2000
DOI: 10.1088/0953-8984/12/26/321
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of ferromagnetic and spin-glass phenomena in La1-xCaxMnO3(0⩽x⩽0.4)

Abstract: Low-field magnetic properties of ceramic La1-xCaxMnO3 (0⩽x⩽0.4) are investigated between T = 5 and 310 K. The paramagnetic-ferromagnetic transition is observed in all the samples. The dependence of the Curie temperature, TC, on x is described within a model of spin polarons associated with electronic localization. Critical behaviour of the susceptibility χ-1(T ) ~ (T-TC)γ is observed for T>TC, with the critical exponents γ = 1.20±0.05 and γ* = 1.64±0.06 below and above the composition x≈0.18 corresponding to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
1
35
0
2
Order By: Relevance
“…Formation of La 2 Zr 2 O 7 , which starts at yϭ0.10 and becomes prominent as y increases further up to yϭ0.40, shifts the stoichiometry towards the higher Ca side and T C is pushed up towards higher temperatures. The variation of T C with mole % of ZrO 2 ͑y͒ matches qualitatively the variation of T C with Ca content ͑x͒ in LCMO as reported by Laiho et al 13 They have reported T C , which varies from around 175 K for xϭ0.0 to around 260 K for xϭ0.40. However our pure LCMO (yϭ0.0) shows lower T C , which may be due to the presence of nonstoichiometric defects such as oxygen ion excess or La ϩ3 , Ca ϩ2 vacancies etc., which results in an increment of electron scattering centers as proposed by Massa et Temperature variations of resistivity between 5 and 375 K of the composites have been shown in Fig.…”
supporting
confidence: 86%
“…Formation of La 2 Zr 2 O 7 , which starts at yϭ0.10 and becomes prominent as y increases further up to yϭ0.40, shifts the stoichiometry towards the higher Ca side and T C is pushed up towards higher temperatures. The variation of T C with mole % of ZrO 2 ͑y͒ matches qualitatively the variation of T C with Ca content ͑x͒ in LCMO as reported by Laiho et al 13 They have reported T C , which varies from around 175 K for xϭ0.0 to around 260 K for xϭ0.40. However our pure LCMO (yϭ0.0) shows lower T C , which may be due to the presence of nonstoichiometric defects such as oxygen ion excess or La ϩ3 , Ca ϩ2 vacancies etc., which results in an increment of electron scattering centers as proposed by Massa et Temperature variations of resistivity between 5 and 375 K of the composites have been shown in Fig.…”
supporting
confidence: 86%
“…LSMFO samples with x¼0.3 and y¼0.15 (#15), 0.20 (#20) and 0.25 (#25) were synthesized with the conventional solid-state reaction method, similar to preparation of La 1À x Ca x MnO 3 [25], from La 2 O 3 , MnO 2 , Fe 2 O 3 and SrCO 3 . The starting materials were precalcined to remove possible adsorbates, weighted in stoichiometric proportions and mixed with subsequent heating in air at 1360 1C for 40 h and intermediate grindings.…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting feature of LSMFO is the magnetic irreversibility, pertinent to frustrated systems such as spin-glasses or cluster-glasses [24], and observed together with the FM transition [20]. Coexistence of the FM and glassy properties has been found in many other manganite perovskites like La 1À x Ca x MnO 3 [25], La 1À x Ca x Mn 1À y Fe y O 3 [23], La 1À x Ba x MnO 3 [26], Nd 0.7 Sr 0.3 MnO 3 [27] and Y 0.7 Ca 0.3 MnO 3 [28], although its connection to the phase separation is not understood well enough.…”
Section: Introductionmentioning
confidence: 98%
“…We find that B K E1 T in # 1À 3 and it lies between $1 À 5 T in # 4, whereas the temperature dependence of the magnetization acquires an upturn below $ 50 K. Only a small deviation of TRM (T) from the difference of M FC (T) À M ZFC (T), following from Fig. 3, indicates an insignificant non-sphericity of magnetic particles [30,31], which is in agreement with the AFM data [24].…”
Section: Macroscopic Magnetic Behaviormentioning
confidence: 64%